Refraining from Imitation: Professional Resistance and Limited Diffusion in a Financial Market - Jonsson, Stefan (Organization Science, 2009)
Why do some practices not spread? Although this is an important question for both diffusion theorists and those interested in institutional change, we know surprisingly little about the limitations on diffusion because most diffusion studies sample on successful diffusion. I address the question of why some practices fail to spread by introducing the concept of a “deviance discount.” A deviance discount is a systematic downgrading of the observed adoption performance of controversial practices, which limits the contagion of such practices. I test and find qualitative and quantitative support for my thesis in the product introduction behavior of Swedish mutual fund firms. My findings hold implications for diffusion theory and theories of endogenous institutional change.